2015
DOI: 10.1177/0883073815579710
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study of the Effects of an Arts Education Program on Executive Function, Behavior, and Brain Structure in a Sample of Nonclinical School-Aged Children

Abstract: The authors examined the effects of arts education on cognition, behavior, and brain of children. Twenty-nine nonclinical children participated in a 15-week arts education program that was composed of either creative movement or musical arts. Children completed the Wisconsin Card Sorting Test, clinical scales, and brain magnetic resonance imaging before and after the intervention. Following program completion, performances on the Wisconsin Card Sorting Test, the Children's Depression Inventory scores, and cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 24 publications
0
14
0
3
Order By: Relevance
“…The results did not identify a significant group effect interaction in ANOVA, yet the completion time for music-trained children was faster. Comparably, 10 studies (three in preschoolers and seven in school-age children) did not identify a significant association between music training and performance in card-sorting tasks or NEPSY subtests (Degé et al, 2011 ; Schellenberg, 2011 ; Park et al, 2015 ; Sachs et al, 2017 ; Frischen et al, 2019 ; Kosokabe et al, 2021 ; Bayanova et al, 2022 ; Chen et al, 2022 ). Once again, the largest study in our review did not identify positive results in the cognitive flexibility tasks among 1,480 children who participated in a year-long, instrument-based education program (Alemán et al, 2017 ).…”
Section: Resultsmentioning
confidence: 94%
“…The results did not identify a significant group effect interaction in ANOVA, yet the completion time for music-trained children was faster. Comparably, 10 studies (three in preschoolers and seven in school-age children) did not identify a significant association between music training and performance in card-sorting tasks or NEPSY subtests (Degé et al, 2011 ; Schellenberg, 2011 ; Park et al, 2015 ; Sachs et al, 2017 ; Frischen et al, 2019 ; Kosokabe et al, 2021 ; Bayanova et al, 2022 ; Chen et al, 2022 ). Once again, the largest study in our review did not identify positive results in the cognitive flexibility tasks among 1,480 children who participated in a year-long, instrument-based education program (Alemán et al, 2017 ).…”
Section: Resultsmentioning
confidence: 94%
“…The Korean version of the Children’s Depression Inventory (CDI) was developed by Cho and Lee ( 29 , 30 ) based on Kovac’s modification of the Beck Depression Inventory for 8–18-year olds ( 31 ). The self-administered instrument is composed of 27 questions on patient feelings.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to inconsistent direct associations between education and cortical thickness, interactions with factors such as exercise have been noted [9]. Very few studies have examined the direct effect of an education intervention on cortical thickness [10] and such studies usually possess only small sample sizes, but education level has been demonstrated to be related to better brain maintenance, i.e. reduced age-related atrophy, and cognitive reserve, but the studies have not been unequivocal [11,12] Both intelligence and educations thickness relations are dwarfed by associations with age and ageing, e.g.…”
Section: Introductionmentioning
confidence: 99%